Textbooks and teaching professionalism - López Hernández, Ana (Avances en Supervisión Educativa, 2007)
Teachers regard text-books’ statements as above discussion, even more, they find in them some kind of self-assurance and a guarantee for professional labour. Since accuracy and specificity are the features on demand about contents, text-books are so much valued as they fulfil this technical conception of teaching, which understands knowledge as something cut-out, finished and not subject to any criticism or revision. Text-books are fundamentally asked to help teachers to transmit contents. However, subjecting the performance of teaching duties to a text-book is a step to miss some professionalism. Teachers think that text-books should make a suitable match to teaching plans instruments -School Stage Project, Classroom Teaching Schedule, etc- but later they admit that the text-book becomes the ruler of the classroom. Either above or at the same level as other teaching elements or schedules, the fact is that text-books still provoke contradictions among teachers, about what they should be and what they really are.